Competences of Adult Learning Facilitators in Community Service Learning: A Review of Literatures - Handrianto, Ciptro; Uçar, Ahmet Serhat; Saputra, Eko; Nengsih, Yanti Karmila; Kenedi, Ary Kiswanto; Rahman, M Arinal (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2021)
Community Service Learning (CSL) is designed to help communities in solving their social problems. The role of adult learning facilitators is important to ensure that all the programs of CSL are running well. This study aims to investigate the competences of adult learning facilitators in community service learning programs. The methodology used in this study is literature review. A total of 85 journal papers were identified by the search machine. However, only 15 articles selected to be reviewed in this study. The result shows that there are five main competences that should be mastered by learning facilitators in community services, such as: Knowledge, Management, Communication, Assessment, and Motivation (KoMCAMo). It can be concluded that the competences of adult learning facilitators play significant role to implement the CSL among community`s members. For recommendation, the future projects related to CSL need to require competent facilitators to enhance participation of community for joining the programs. The regular trainings are encouraged to adult learning facilitators to create an effective CLS`s program.